Identification and Characterization of Microsatellite Markers Derived from the Whole Genome Analysis of Taenia solium. - Mónica J Pajuelo; María Eguiluz; Eric Dahlstrom; David Requena; Frank Guzmán; Manuel Ramirez; Patricia Sheen; Michael Frace; Scott Sammons; Vitaliano Cama; Sarah Anzick; Dan Bruno; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Infections with Taenia solium are the most common cause of adult acquired seizures worldwide, and are the leading cause of epilepsy in developing countries. A better understanding of the genetic diversity of T. solium will improve parasite diagnostics and transmission pathways in endemic areas thereby facilitating the design of future control measures and interventions. Microsatellite markers are useful genome features, which enable strain typing and identification in complex pathogen genomes. Here we describe microsatellite identification and characterization in T. solium, providing information that will assist in global efforts to control this important pathogen. METHODS:For genome sequencing, T. solium cysts and proglottids were collected from Huancayo and Puno in Peru, respectively. Using next generation sequencing (NGS) and de novo assembly, we assembled two draft genomes and one hybrid genome. Microsatellite sequences were identified and 36 of them were selected for further analysis. Twenty T. solium isolates were collected from Tumbes in the northern region, and twenty from Puno in the southern region of Peru. The size-polymorphism of the selected microsatellites was determined with multi-capillary electrophoresis. We analyzed the association between microsatellite polymorphism and the geographic origin of the samples. RESULTS:The predicted size of the hybrid (proglottid genome combined with cyst genome) T. solium genome was 111 MB with a GC content of 42.54%. A total of 7,979 contigs (>1,000 nt) were obtained. We identified 9,129 microsatellites in the Puno-proglottid genome and 9,936 in the Huancayo-cyst genome, with 5 or more repeats, ranging from mono- to hexa-nucleotide. Seven microsatellites were polymorphic and 29 were monomorphic within the analyzed isolates. T. solium tapeworms were classified into two genetic groups that correlated with the North/South geographic origin of the parasites. CONCLUSIONS/SIGNIFICANCE:The availability of draft genomes for T. solium represents a significant step towards the understanding the biology of the parasite. We report here a set of T. solium polymorphic microsatellite markers that appear promising for genetic epidemiology studies.